Interaction between Dark Matter and Dark Energy and the Cosmological Coincidence Problem - Kourosh Nozari; Noushin Behrouz; Narges Rashidi (Advances in High Energy Physics)
We consider a quintessence model of dark energy inspired by scalar-tensor theories of gravity where the scalar field is nonminimally coupled to gravity and dark matter. By considering exponential potential as self-interaction potential, the stability and existence of the critical points are discussed in details. With nonminimally coupled dark sector with gravity, we obtain scaling solutions to address the coincidence problem by considering complex velocity for dark matter. The statefinder diagnostic shows that the equation of state reaches ΛCDM model in the future.